2005
DOI: 10.1002/mrc.1707
|View full text |Cite
|
Sign up to set email alerts
|

Full multinuclear resonance analysis of 4-amino-1,1,2,2,9,9,10,10-octafluoro[2.2]paracyclophane

Abstract: The complete assignment of 19F, 1H and 13C NMR spectra for a monosubstituted octafluoro[2.2]paracyclophane derivative is described for the first time. The unambiguous assignments were achieved through the combination of 19F--1H HOESY, 1H COSY and 19F COSY techniques and then further confirmed employing a complementary approach using a Karplus-dependent 3JCF interaction. Interesting aspects of the coupling patterns for various JHH, JHF, JCF and JFF interactions are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The amide hydrogen (δH = 10.05 ppm in d 6 -acetone) revealed some isotopic exchange from the deuterated acetone solvent used, but it was still possible to easily detect the NH to F-2s correlation in the HOESY experiment; www.interscience.wiley.com/journal/mrc the CF 3 resonance (δF = −77 ppm) showed a through-space coupling to F-1s (in benzene-d 6 the CF 3 signal appeared as a 2. of resonances. However, the effect of isotopic exchange of the amide hydrogen was very noticeable in both deuterated acetone and benzene, and as previously described for a related system, [14] this deuterium isotope effect [19] caused a shift in chemical shift for F-2s, F-1s and H-5. This phenomenon revealed itself as either causing certain signals to appear as poorly resolved multiplets, or sometimes even as separate peaks (e.g.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…The amide hydrogen (δH = 10.05 ppm in d 6 -acetone) revealed some isotopic exchange from the deuterated acetone solvent used, but it was still possible to easily detect the NH to F-2s correlation in the HOESY experiment; www.interscience.wiley.com/journal/mrc the CF 3 resonance (δF = −77 ppm) showed a through-space coupling to F-1s (in benzene-d 6 the CF 3 signal appeared as a 2. of resonances. However, the effect of isotopic exchange of the amide hydrogen was very noticeable in both deuterated acetone and benzene, and as previously described for a related system, [14] this deuterium isotope effect [19] caused a shift in chemical shift for F-2s, F-1s and H-5. This phenomenon revealed itself as either causing certain signals to appear as poorly resolved multiplets, or sometimes even as separate peaks (e.g.…”
mentioning
confidence: 61%
“…[13] To this end, in 2005 we published the first full multinuclear magnetic resonance analysis of a mono substituted OFP derivative (2a). [14] The amino substituted molecule was judiciously selected for the first full assignment due to its well-resolved peaks and excellent response to H-F based nuclear Overhauser effect (nOe) experiments. However, not all the compounds studied were so responsive, and here we describe refinements and alternative strategies of the previous protocol, [14] leading to the unambiguous assignments of the 1 H and 19 F resonances of four monosubstituted and six pseudo ortho di-substituted derivatives of OFP, and also revealing interesting solvent effects and noteworthy coupling patterns for various J HH , J HF , and J FF interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than that, the chemical shifts do not follow the trend seen in the only previous case of assignment of the bridge fluorines, 4-amino-AF4. [12] Simple inspection of the fluorine spectrum, the 19 F-19 F DQF-COSY spectrum, and the fluorine spectrum with selective decoupling of F4 and with broadband proton decoupling (Fig. 6(S)) all demonstrate that the aromatic fluorine couples with the two syn bridge fluorines from the closest tetrafluoroethylene unit with a coupling of ca.…”
Section: F-af4 (1)mentioning
confidence: 96%
“…It was only recently that such an assignment was made possible, based on the nOes between the bridge fluorines and the aromatic protons. [12] Due to the novelty of the system, there are no fluorine SCS for the PFPCs, neither for the bridge nor for the aromatic fluorines, that could help in solving the regiochemistry of the di-, tetra-and hexa-substituted PFPCs. In all these compounds, however, 19 F-19 F DQF-COSY and selective decoupling of 19 F spectra indicated that an aromatic fluorine couples with two fluorines of two distinct difluoromethylene groups of the same tetrafluoroethylene unit.…”
Section: 2]paracyclophane ([22]pcpmentioning
confidence: 99%